(untitled) (The Pakistan Development Review, 1978)
The present paper is an extension of an earlier study on "Labour Content and Structure of Pakistan’s Manufactured Exports". While in the former study a partial method (labour employed in home goods sectors only) was used to estimate the total labour requirements of exports, the present paper takes into account all the inter-industry linkage effects to calculate total labour requirements for manufactured exports as well as for manufactured imports. The basic aim of this study is to seek the verification of the HeckscherOhlin (H-O) theorem with respect to Pakistan’s trade of manufactured goods, i.e., to test whether Pakistan’s exports are relatively more labour intensive than her imports or not? The paper has been divided into four sections. The first section describes the methodology and data, while the second summarizes and analyses the final results. An international comparison of labour intensity has been made in the third section,• whereas the last section discusses the conclusions and policy implications.